In Situ Electrochemical Dilatometry Study of (De)lithiation and Polysulfide Dissolution-Induced Dimensional Changes in Lithium-Sulfur Cathodes during Charging and Discharging. Issue 5 (9th January 2020) - Li, Manni; Wang, Zeyu; Detsi, Eric
Abstract : In this work we use in situ electrochemical dilatometry techniques to demonstrate the existence of two distinct dimensional change mechanisms in lithium-sulfur cathodes during cycling, namely a reversible dimensional change occurring due to the difference in density between pure sulfur and lithiated sulfur compounds, and an irreversible shrinkage associated with polysulfide dissolution into the electrolyte. Our results contribute to elucidate the failure mechanism of lithium-sulfur cathodes, and the new insight can be used to improve the cycle-life of lithium-sulfur batteries. Indeed, while the reversible dimensional changes are fundamentally unavoidable, the irreversible dimensional changes can be mitigated by preventing the loss of active materials during cycling, which should obviously improve the battery cycle-life.